Trauma Healing Therapy for Post-Earthquake Children Using Traditional Randai Approach - Jumilia, Jumilia; Kanathasan, Jayasree S. (International Journal of Nursing Information, 2024)
Earthquake disasters can significantly impact the psychological well-being of victims across all age groups, particularly children. As a vulnerable group, children face unique challenges in coping with disaster situations due to their limited abilities, resources, and immature psychological adaptations. Various interventions have been explored to address disaster-related trauma in children. In Indonesia, Randai, a traditional cultural performance, is believed to help reduce psychological trauma in children. This study aims to evaluate the effectiveness of Randai therapy in alleviating psychological trauma among children affected by earthquakes. A quantitative approach was employed using a pre-experimental study design with pretest-posttest assessments. The sample size is 202 respondents, consisting of 101 for the Randai intervention group and 101 for the control group. The results of this study showed a pretest score for trauma level of 25.61 before Randai therapy and a posttest score of 20.96 after Randai therapy. There is a significant difference between the psychological trauma of respondents before and after being given Randai therapy, with an average value of 25.61 with a standard deviation of 7.800 and an average value of 20.96 with a standard deviation of 7.511 respectively. It was found that Randai therapy had positively reduced psychological trauma among children after the earthquake (p-value < 0.05). Randai therapy is significant in reducing psychological trauma in children after the earthquake in Kajai West Pasaman, West Sumatra. This study contributes by revealing the effectiveness of traditional Randai therapy as a non-pharmacological therapy to reduce post-disaster children's psychological trauma. In addition, it enriches the culture-based approach to safe, affordable, and sustainable psychological recovery.